Investigating Surface Deformation Caused by Excavation of Curved Shield in Upper Soft and Lower Hard Soil - Jia, Bao-Xin; Gao, Zong-xian (Frontiers in Earth Science, 2022)
Existing studies on surface deformation prediction consider single soil layers and straight-line excavation when investigating deformation caused by metro shield construction. In this study, we provide a new prediction method for studying the soil deformation caused by curved shield tunnel construction in the upper soft and lower hard soil. The deformation equations are derived using the Mindlin solution and random medium theory and are verified using engineering examples and numerical simulation. The influencing factors and laws of the surface deformation caused by the excavation are also identified. The study found that the horizontal settlement trough on the ground surface was distributed asymmetrically during the curve construction, with maximum settlement on the inner side of the curve. The offset and settlement values were affected by the thrust difference coefficients α and β and the turning radius. When constructing in the upper soft and lower hard soil layers, the settlement trough tends to become wider and shallower. The results show that the derived equation is suitable for actual engineering calculations, and the measured data are in good agreement.